Nonpharmacological prevention of osteoporotic fractures - Cathy R Kessenich (Dove Medical Press, 2007)
Cathy R KessenichDepartment of Nursing, University of Tampa, Tampa, FL 33606, USA; Nurse Practitioner, Private Practice, Tampa, FLAbstract: Osteoporosis is a systemic, metabolic disease that can result in debilitating fractures. The lasting effects of vertebral and hip fractures can cause acute and chronic pain, deformity, and emotional distress. Research evidence and clinical experience have determined that weight bearing and strength training exercise, fall prevention efforts, hip protectors, and some alternative therapies may assist patients in avoiding the pervasive and lasting effects of osteoporotic fractures. Clinicians should consider the recommendations of nonpharmacological measures to assist patients at risk for experiencing the culminating event of this destructive disease.Keywords: osteoporosis, osteoporotic fracture, osteoporosis prevention